Mixed features specifier in mood disorder: The prevalence and associated factors / Tesini M. Paramannantha Veloo - Tesini, M. Paramannantha Veloo (2020)
Introduction: Mixed episode has been an unrelieved source of discussion in the field of psychiatry over the course of two decades as the DSM-IV criteria for both a depressive and manic episode had to be fulfilled to make this diagnosis. Nevertheless, in practice, this threshold was demonstrated to be too high. Therefore, the DSM-5 introduced a less stringent ‘specifier’ in which three symptoms of the opposite pole suffice thereby creating depression and mania with mixed features, respectively. Literatures points out that approximately 40% of patients have mixed episodes, but this figure may be much higher within the context of DSM-5. Literatures have persistently showed that major mood disorders such as Major Depressive Disorder and Bipolar Disorder with Mixed features are associated with a poorer outcome and a more complex progress of illness. Methodology: This is a cross sectional prevalence study to determine the prevalence of Mixed Features Specifiers among Major Mood Disorder and its associated factors among outpatient patients. Study was done in Hospital Bahagia Ulu Kinta, Perak using a researcher administered questionnaire which consisted of five parts which includes sociodemographic factors, clinical characteristics, MADRS score, YMRS score and QoL score. All data was analyzed using SPSS version 24.0. Results: A total of 148 patients were selected as calculated in the sample size calculation for this study. Overall prevalence of MFS among Major Mood Disorder was 29.8%. There were significant associations between ethnicity (X2=9.063; df 1; p=0.028), marital status (X2=18.738; df 1; p<0.001) and average monthly income (X2=31.534; df 1; p=<0.001) with MFS. In terms of clinical characteristics, there were significant associations between number of hospitalizations (X2=41.026; df 1; p<0.001), trials of medications (X2=29.540; df 1; p<0.001), total number of medications on (X2=42.338; df 1; p<0.001), history of ECT (X2=10.590; df 1; p=0.001), family history of mood disorder (X2=20.944; df 1; p<0.001), suicidal attempts (X2=26.570; df 1; p<0.001), history substance use (X2=19.249; df 1; p<0.001), compliance to treatment (X2=4.310; df 1; p=0.038), YMRS score (X2=16.799; df 1; p=0.001) and MADRS score (X2=43.525; df 1; p<0.001) with MFS. From the results that we obtained, it could identify some associated with MFS which were significant in the sociodemographic factors and clinical characteristics such as amount of income, substance use and number of hospitalizations. Conclusion: As a conclusion, we fail to reject the alternate hypothesis that there are sociodemographic and clinical characteristics associations with MFS. We also failed to reject the alternate hypothesis that there are significant differences between the QoL of MFS patients and non MFS patients. Keywords: Mixed Features Specifiers (MFS), Major Mood Disorder, Quality of Life (QoL)